Effect of surface treatment on molecular alignment behavior by scanning wave photopolymerization. (13th March 2019) - Ishizu, Masaki; Aizawa, Miho; Akamatsu, Norihisa; Hisano, Kyohei; Fujikawa, Shigenori; Barrett, Christopher J; Shishido, Atsushi
Abstract: Alignment of anisotropic molecules can provide high-performance display materials, and can be achieved by using a photoresponsive alignment layer. By contrast, scanning wave photopolymerization (SWaP) based on molecular diffusion offers direct alignment of liquid crystal (LC) polymers without the need for polarized light or photoreactive dyes. By demonstrating this alignment method on a variety of templates to compare surface conditions with and without alignment layers, we present a process to align LCs regardless of surface treatment, even in the opposite direction of surface rubbing, indicating that SWaP enables robust and facile molecular alignment.